STUDI LITERATUR: MENDORONG MINAT BELAJAR PJOK PESERTA DIDIK SEKOLAH DASAR MELALUI KEGIATAN PERMAINAN TRADISIONAL - Fadhlil Hadi; Septian Raibowo; Yahya Eko Nopiyanto; Nurul Fajar Muslimah Ningrum; Arrendi Afrilliyan; Nur Fathanah (Journal of Physical Activity and Sports (JPAS), 2025)
Physical Education, Sports, and Health is an important subject in Elementary School that aims to improve the knowledge, skills, physical, spiritual, and social health of students. However, in reality, many students are still less interested in studying Physical Education, Sports, and Health. This is caused by several things, including boredom, minimal game variety, and boring and uninteresting teaching strategies. This study seeks to determine how effective the use of traditional games in increasing students' interest in learning. This research is qualitative using a literature study method through library sources such as books, modules, journals, and scientific works. According to the results of the study, the use of traditional games in Physical Education, Sports, and Health lessons can increase the interest in learning of Elementary School students. Considering that Physical Education, Sports, and Health is an important subject in Elementary School that aims to improve students' motor skills, knowledge, skills, social skills, and physical health.